Emerging themes in food security: environmental justice, extended families and the multiple roles of grandmothers - Ethel Alderete; Lauren Sonderegger; Eliseo J. Pérez-Stable (BMC, 2018)
Abstract Background Pre- and perinatal nutritional status defines the development of adult metabolism and energy balance in humans. Young children in poor households are disproportionately more vulnerable to food insecurity given the cumulative impact of chronic stress on susceptibility to chronic diseases as an adult. Qualitative studies focusing on the experience of food insecurity in Latin America are scarce. In Argentina, although socioeconomic indicators improved in the aftermath of the 2001ecomomic crisis, the disadvantaged provinces in the north continue to bear the burden of historical inequities. The study was conducted among Primary Health Care patients in the city of San Salvador de Jujuy, Argentina. It analyzes environmental and household level stressors through the narratives of mothers with young children living with food insecurity, from the perspectives of eco-developmental conceptual frameworks. Methods We conducted 11 semi-structured interviews with mothers of children < 1 to 6 years of age who participated in maternal-child health programs in Primary Health Care clinics and lived in food insecure households. Interviews focused on the environmental context and the resources and processes for obtaining and preparing daily meals. Results The Eco-bio-developmental (EBD) framework and the vulnerability-assets approach, provided a basis for conceptualizing the significance of findings. Our results indicated the need to understand pathways in the association of stressors, vulnerability and ill health, as well as the mitigating role of social relationships. For example, understanding the link between the stress of being exposed to environmental contaminants and the capacity to overcome food insecurity, or developing strategies to integrate the support provided by kinship networks like extended families into food security programs. The results also indicate the importance of developing support mechanisms for vulnerable family members like grandmothers in food insecure households who play instrumental roles as providers and caretakers of younger relatives. Conclusion The empirical evidence generated by this study may inform community based strategies and public health policies to address food insecurity in vulnerable population groups who face health effects from multiple stressors.